Empowerment through mine community development: how the politics of development perpetuate poverty in mining areas – a legal theoretical analysis - Heyns, Anri (Department of Private Law, 2021)
The Mineral and Petroleum Resources Development Act (“MPRDA”) and the Broad-Based Socio-Economic Empowerment Charter for the South African Mining and Minerals Industry (“Mining Charter”), created in terms of the MPRDA, aim to address the exploitative legacies of past discriminatory practices in the mining industry. Impoverished mining communities stand to benefit from empowerment under the Mining Charter in the form of mine community development – one of the elements that constitute a mining right holder's commitment under the Mining Charter. Despite this legislative intervention and the relative wealth generated by the extraction of mineral resources, poverty and conflict have become the stereotypical images associated with mining areas. This project aims to determine why the empowerment of mining communities through mine community development perpetuates poverty from the past and creates new inequalities. To answer this main question, it is considered how the historical context within which the relevant policy and legislation were created, affected legislative drafting. Second, the effects of promoting development and empowerment in legislative provisions are explored to determine which worldviews and underlying values are being promoted by the legislative instruments under discussion. Furthermore, it is considered how these worldviews and underlying values affect how mining communities, subjected to harsh socio-economic living conditions, are depicted in legislative provisions. Here, it is specifically considered what the notion of “community” signifies in a development context and how “community” is represented in legislation. The thesis is a theoretical exposition of the ideological assumptions underlying the concepts “development”, “empowerment”, “community” and “poverty”. It is shown that “mine community development” is an inherently contradictory notion in South African law. The development paradigm implies the universalisation of values, effectively creating “the poor”, and causing vagueness and paradoxes. It results not only in a perpetuation of poverty and inequality from the past but also in the creation of new inequalities, as is evident in the differentiation drawn by the Mining Charter between different types of communities in mining areas. Measures currently being enforced by the legislation under discussion, are in desperate need of reconsideration.